Comparing Dual-Zone Immediate Implant Placement and Socket Shield Technique for Ridge Width Changes in the Maxilla: A Prospective Cohort Study - Shadid RM (Dove Medical Press, 2022)
Rola Muhammad Shadid1,2 1Department of Prosthodontics, Faculty of Dentistry, Arab American University, Jenin, Palestinian Territory; 2Private Practice, Palestine, Palestinian TerritoryCorrespondence: Rola Muhammad Shadid, Department of Prosthodontics, Faculty of Dentistry, Arab American University, P.O Box: 240, Jenin, Palestinian Territory, Tel +970 594494066, Email rola.shadid@aaup.eduPurpose: The aim of this prospective cohort study was to assess the facial-palatal ridge dimensional changes that occurred at 8- 10 months following flapless dual-zone (DZ) immediate implant placement and socket-shield (SS) immediate placement in the maxilla.Materials and Methods: A total of 19 patients who received 20 implants were included, with 10 implants (MegaGen AnyRidge) placed for each treatment, DZ and SS. Cast models were made at 8- 10 months after implant placement to assess the dimensional ridge changes by measuring the facial-palatal ridge width on implant sites (T) at six designated points starting from the gingival margin (0, 1, 2, 3, 5 and 7) and comparing it with the corresponding measurement on the contralateral tooth site (C).Results: All 20 implants demonstrated successful osseointegration at 8- 10 months follow-up (survival rate 100%). Two out of ten cases of SS group presented with minor manageable complications of external shield exposure. DZ group showed an average of 0.3 mm facial-palatal ridge width reduction, while SS group revealed a mean gain in ridge width of approximately 0.2 mm at 8- 10 months follow-up.Conclusion: When comparing between two treatments, there was a significant difference in ridge width change at 8- 10 months following implant placement, indicating better preservation of the ridge contour for socket shield technique.Keywords: follow-up studies, investigative techniques, dental implantation, osseointegration